Altererythrobacter lutimaris sp. nov., a marine bacterium isolated from a tidal flat and reclassification of Altererythrobacter deserti, Altererythrobacter estronivorus and Altererythrobacter muriae as Tsuneonella deserti comb. nov., Croceicoccus estronivorus comb. nov. and Alteripontixanthobacter muriae comb. nov. Issue 12 (7th December 2021) - Kim, Dongjun; Yoo, Yeonjae; Khim, Jong Seong; Yang, Dongmin; Pathiraja, Duleepa; Park, Byeonghyeok; Choi, In-Geol; Kim, Jae-Jin
Abstract : A yellow-coloured bacterium, designated strain JGD-16 T, was isolated from a tidal flat in Janggu-do, Garorim Bay, Taean-gun, Chungcheongbuk-do, Republic of Korea. Cells were Gram-stain-negative, aerobic, non-flagellated and short ovoid to coccoid-shaped. Growth was observed at 10–37 °C (optimum, 30 °C), pH 6.0–9.0 (pH 8.0) and with 1–5% (w/v) NaCl (2%). Results of 16S rRNA gene sequence analysis indicated that strain JGD-16 T was closely related to Altererythrobacter xiamenensis LY02 T (97.1 %), Altererythrobacter aurantiacus O30 T (96.3 %), Altererythrobacter ishigakiensis JPCCMB0017 T (95.8 %), Altererythrobacter epoxidivorans JCS350 T (95.7 %) and Altererythrobacter insulae BPTF-M16 T (95.3%). Phylogenomic analysis using the maximum-likelihood algorithm showed that strain JGD-16 T formed a clade with the genus Altererythrobacter . The genomic DNA G+C content was 57.8 mol%. The predominant respiratory quinone was ubiquinone-10. The major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylcholine, a sphingoglycolipid, an unidentified glycolipid and an unidentified lipid. The major fatty acids were C18:1 ω 7 c (31.5 %) and C18:3 ω 6 c (19.6 %). On the basis of its phylogenomic, physiological and chemotaxonomical characteristics, strain JGD-16 T represents a novel species within the genus Altererythrobacter, for which the name Altererythrobacter lutimaris JGD-16 T sp. nov. is proposed. The type strain is JGD-16 T (=KCTC 72632 T =KACC 21405 T =JCM 33750 T ). We also propose the reclassification of Altererythrobacter deserti as Tsuneonella deserti comb. nov., Altererythrobacter estronivorus as Croceicoccus estronivorus comb. nov. and Altererythrobacter muriae as Alteripontixanthobacter muriae comb. nov.